The heart of music classification: toward a model of classifying musical medium. Issue 2 (24th January 2018) - Lee, Deborah; Robinson, Lyn
Abstract : Purpose: The purpose of this paper is to understand the classification of musical medium, which is a critical part of music classification. It considers how musical medium is currently classified, provides a theoretical understanding of what is currently problematic, and proposes a model which rethinks the classification of medium and resolves these issues. Design/methodology/approach: The analysis is drawn from existing classification schemes, additionally using musicological and knowledge organization literature where relevant. The paper culminates in the design of a model of musical medium. Findings: The analysis elicits sub-facets, orders and categorizations of medium: there is a strict categorization between vocal and instrumental music, a categorization based on broad size, and important sub-facets for multiples, accompaniment and arrangement. Problematically, there is a mismatch between the definitiveness of library and information science vocal/instrumental categorization and the blurred nature of real musical works; arrangements and accompaniments are limited by other categorizations; multiple voices and groups are not accommodated. So, a model with a radical new structure is proposed which resolves these classification issues. Research limitations/implications: The results could be used to further understanding of music classification generally, for Western art music and other types of music. Practical implications: The resulting model could be used to improve and design new classification schemes and to improve understanding of music retrieval. Originality/value: Deep theoretical analysis of music classification is rare, so this paper's approach is original. Furthermore, the paper's value lies in studying a vital area of music classification which is not currently understood, and providing explanations and solutions. The proposed model is novel in structure and concept, and its original structure could be adapted for other knotty subjects.